The future of neurology in Europe. Issue 1 (19th June 2017) - Deuschl, Günther
This is a viewpoint on future developments opportunities and risks for the healthcare of neurological patients. The discipline started with the method of clinical pathologic correlations which has discovered most of the major neurological diseases in the first half of the last century. In the second half research in our field was merged with the one of basic neurosciences currently labeled as translational neurosciences. This period began with the development of neurophysiology and imaging techniques which allow characterizing the status of the nervous system in health and disease. Later molecular, genetic and many other techniques gained importance for our field. These tools improving the understanding of pathogenesis and diagnosis have been instrumental, but the importance of our field came to the attention of the general population only when new therapies were developed based on these advances. This lead to the establishment of neurological departments both at University level and in general hospitals. This ongoing process has made neurology nowadays the third largest discipline for patient care alongside with internal medicine and surgery in many places. No need to say that further specialization within neurology is needed but the discipline as a whole must operate as an entity to make sure that patient care and subspecialist development run in harmony and neurologists can still also practice as general neurologists. The European Academy of Neurology is supporting these efforts. In the future the best strategy to help neurological patients will be to even increase the research to understand neurological diseases and to develop new therapies.